(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2023)
In this article, information on the effects of drought on the growth trends and leaf area expansion of widely regionalized cotton cultivars in Uzbekistan was presented. It was found that the growth trends and the expansion of the leaf surface of the studied cotton varieties depend on the soil moisture level. It was observed that the varieties of cotton Bukhara-8, and Bukhara-102 are resistant to drought compared to the variety S-6524. According to the obtained scientific results, as a result of the effects of drought, it was found that the growth slowed down and the leaf area decreased in the studied varieties. Among the studied varieties, it was found that the growth rate of the Bukhoro-102 variety and the expansion of the leaf surface are higher than Bukhoro-8 and S-6524 varieties.